2012
DOI: 10.1057/imfer.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

The Vulnerability of Sub-Saharan Africa to Financial Crises: The Case of Trade

Abstract: Motivated by the 2008-2009 financial crisis and the trade collapse, we analyze the effect of past banking crises on trade with a focus on African exporters. We show that they are particularly vulnerable to a banking crisis in the countries they export to. We distinguish between an income effect (during a banking crisis, income and exports to the country fall) and a disruption effect (a banking crisis disrupts the financing of trade channels). For the average country, the disruption effect is moderate (a devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 36 publications
(21 reference statements)
2
54
0
6
Order By: Relevance
“…Some studies suggested that trade was considered to be the most important crisis transmission for the region (see, for example, ODI, 2010;Berman and Martin, 2012). There are two mechanisms through which a financial crisis in the developed countries can affect the export of other countries.…”
Section: Tradementioning
confidence: 99%
See 2 more Smart Citations
“…Some studies suggested that trade was considered to be the most important crisis transmission for the region (see, for example, ODI, 2010;Berman and Martin, 2012). There are two mechanisms through which a financial crisis in the developed countries can affect the export of other countries.…”
Section: Tradementioning
confidence: 99%
“…The first one is the income effect due to the sharp economic recession brought by the crisis. The second one is the disruption effect in the form of fall in trade finance (Berman and Martin, 2012). In the case of the sub-Saharan African countries, Berman and Martin (2012) found that African exports were more sensitive to large decline in income of their trading partners.…”
Section: Tradementioning
confidence: 99%
See 1 more Smart Citation
“…H4: the income, price and monetary shocks of (A) and the price of raw materials shocks impact the external variables enumerated in H3 [32][33][34][35][36][37][38][39].…”
Section: Model Formalizationmentioning
confidence: 99%
“…While the financial crisis originated in high income countries, its effects on trade were rapidly transmitted to low-income countries. It has been hypothesized that the effects of constrained trade finance could vary by exporter income (Malouche 2009, Berman andMartin 2010) and by geographic region (Berman and Martin 2010 Table 4 and figure 6 present the main decomposition along these income definitions.…”
Section: Heterogeneity and Mechanismsmentioning
confidence: 99%